Heme Oxygenase-1 Promotes Delayed Wound Healing in Diabetic Rats - Qing-Ying Chen; Guo-Guang Wang; Wei Li; Yu-Xin Jiang; Xiao-Hua Lu; Ping-Ping Zhou (Journal of Diabetes Research)
Diabetic ulcers are one of the most serious and costly chronic complications for diabetic patients. Hyperglycemia-induced oxidative stress may play an important role in diabetes and its complications. The aim of the study was to explore the effect of heme oxygenase-1 on wound closure in diabetic rats. Diabetic wound model was prepared by making an incision with full thickness in STZ-induced diabetic rats. Wounds from diabetic rats were treated with 10% hemin ointment for 21 days. Increase of HO-1 protein expression enhanced anti-inflammation and antioxidant in diabetic rats. Furthermore, HO-1 increased the levels of VEGF and ICAM-1 and expressions of CBS and CSE protein. In summary, HO-1 promoted the wound closure by augmenting anti-inflammation, antioxidant, and angiogenesis in diabetic rats.